Dead men tell no tales : traumatized male bodies in Salman Rushdie’s Midnight’s Children and Arundhati Roy’s The God of Small Things. - Sofia Begum Mohammad Sultan. (2013)
The institutions within which the characters in the novel are located favour or give emphasis to the feminine bodies, empowering them in the narrative. Several male bodies in the novel are broken and split, silenced in the process, removing them completely, making the novels’ presentation of history imbalanced. However, in addition to sidelining these male bodies, they are subjects of trauma. This paper would argue that these male bodies have been sidelined in these novels, as a way of speaking for history in the claims of the feminine voice that has long been suppressed by patriarchy. These under-represented male bodies are left out in an inversely proportionate relationship to the feminine bodies. With a recent growth of attention and empowerment to the feminine voice and bodies by extension, the male bodies have been left out in their equal claim for history.